Performing Global at IntelStar: Figuring the Call Center on Manila Stage - Tiatco, Sir Anril Pineda (Archīum Ateneo, 2024)
Set in Makati, the central business district of the National Capital Region, Welcome to IntelStar is a monodrama satirizing the call center industry in the Philippines. The performance is an exemplar in positioning a diasporic consequence of globalization vis-à-vis nationalism because it calls on a national sentiment to the extent that the play illustrates resistance to globalization’s economic and neoliberal attachments, often perceived as the destructive force of cultural diversity and uniqueness. In relation, the performance used a recurring trope in Philippine culture, which is called in the essay as the Americanization issue: the conception of the Filipino/a as a master mimic of other cultures, particularly the American one. Overall, Welcome to IntelStar falls short in its criticism of globalization because it isolated the phenomenon within the politics of the market. But nevertheless, the play allows the Filipino body, through its protagonist Chelsea, to be “visible.” With her “expertise” at imitation, Chelsea’s visibility destabilizes the global order. Chelsea’s mimicry is not simply about wanting to be like those who are imitated, but a strategy to assert a sense of self. This imitative performance implies self- consciousness and intimacy to the one being imitated. In this way, mimicry as self- actualization is a creative strategy and has the potential to overthrow hierarchies of globalization in neo-colonial and neo-imperial orders.